Cerebro-spinal fluid lactate concentration in neurologically normal and abnormal children - Yalaz, Kalbiye (The Turkish Journal of Pediatrics, 1970)
In this paper the importance of lactate values in CSF in the diagnosis of neurologically normal and abnormal children has been studied from a total of 110 patients including a control group of 20. A statistically significant difference was found between the mean value among the various groups and that of normal children. The lactate values in CSF can be of significant value in the diagnosis of various types of brain damaged and neurological diseases in children.